Advanced Springback Compensation Strategy through elimination of avoidable elastic strain energy. Issue 1 (1st May 2022) - Birkert, A; Zimmermann, P; Hartmann, B; Nowack, M
Abstract: The stamping of dimensionally accurate sheet metal body components still represents a huge challenge in the automotive industry. This is partly caused by the multi-stage production process which complicates the design of an appropriate compensation strategy dramatically. A key prerequisite of an appropriate compensation strategy is to eliminate any undesired influence of elastic energy being potentially induced when closing the blankholders in the several operations throughout the production process. Here, a universally applicable compensation strategy is presented which fulfils this requirement thoroughly; by applying this process, the involved strain energy is reduced to a minimum due to proper part position in all operations. Technically this compensation strategy is achieved by, first, simulating all operations of the stamping process individually, second, by individually calculating the springback after each operation and, third, by accumulating the calculated deviation vector fields for each operation appropriately, which are then used for springback compensation. The process is time and cost effective and the required efforts are moderate even for complicated multistage stamping operations.